Child and adolescent access to mental healthcare: from CAPSi to Health Conferences - Cubas, João Mario; Bonamigo, Victoria Grassi; Alvarenga, Rodrigo; Carvalho, Deborah Ribeiro (Argumentum, 2022)
This article analyzes how the perceptions of professionals from Child Psychosocial Care Centers, regarding children’s access to mental health services, affects the guidelines of Health Conferences. Field research was carried out through interviews with a semi-structured script, allied to documentary research and reports from Health Conferences. The findings are discussed based on the concepts of deliberative democracy and communicative action, proposed by Jürgen Habermas. It was observed that the perceptions of professionals are not evident in the reports, as well as evidence of the existence of a barrier of understanding concerning children’s mental health, and that the alterity of children and adolescents may be denied because of the absence of a democratic and deliberative perspective in the development of public policies.